Melt-based compression-molded scaffolds from chitosan-polyester blends and composites: Morphology and mechanical properties - Correlo, V. M. (2009)
Blends of chitosan and synthetic aliphatic polyesters (polybutylene succinate, polybutylene succinate adipate, polycaprolactone, and polybutylene terepthalate adipate) were compounded with and without hydroxyapatite, a bioactive mineral filler known to enhance osteoconduction. The blends and composites were compression molded with two different granulometric salt sizes (63–125 lm and 250–500 lm) having different levels of salt content (60, 70, and 80%) by weight. By leaching the salt particles, it was possible to produce porous scaffolds with distinct morphologies. The relationship between scaffold morphology and mechanical properties was evaluated using scanning electron microscopy, microcomputed tomography, compression testing, differential scanning calorimetry, small-angle X-ray scattering (SAXS), and wide-angle X-ray scattering. The produced scaffolds are characterized by having different morphologies depending on the average particle size and the amount of NaCl used. Specimens with higher porosity level have a less organized pore structure but increased interconnectivity of the pores. The stress–strain curve under compression displayed a linear elasticity followed by a plateau whose characteristics depend on the scaffold polymer composition. A decrease in the salt particle size used to create the porosity caused in general a decrease in the mechanical properties of the foams. Composites with hydroxyapatite had a sharp reduction in yield stress, modulus, and strain at break. The melting temperature decreased with increased chitosan content. SAXS results indicate no preferential crystalline orientation in the scaffolds. Cytotoxicity evaluation were carried out using standard tests (accordingly to ISO/ EN 10993 part 5 guidelines), namely MTS test with a 24-h extraction period, revealing that L929 cells had comparable metabolic activities to that obtained for the negative control.